Political Clientelism in Presidential Elections: Voting Behaviour and Social Assistance - Noor, Moch.; Hidayaturrahman, Mohammad; Putu Sugiantiningsih, Anak Agung (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
Clientelism is a dangerous practice for democratic countries as it exploits poverty for elections. Despite the risks associated with clientelism, political actors in various countries continue to engage in it in election campaigns to win political contests. This study aims to understand voter behaviour and clientelism in the 2024 Indonesian presidential election. The study focuses on the use of the government's social assistance in “election campaigns” and how it impacts voter behaviour. This study uses mixed methods, quantitative surveys before the 2024 presidential election, and qualitative analysis, especially content analysis of documents in online media. The study revealed that clientelism in the form of social assistance impacts voter behaviour. The findings also show four critical factors: the timing of the distribution of social assistance, direct distribution of social assistance by the president, the current economic condition of the community, and the form of social assistance in cash and basic needs. The study contributes to the theory of voter behaviour by shaping voter behaviour outside the aspect of the voter, such as economic factors. Empirically, this research is also helpful for improving the regulations or laws of general elections in Indonesia, which can improve the governance of social assistance to avoid being used as a means of campaigning by incumbent officials.